Study on thermal and erosive wear behaviour of hard powders filled glass-epoxy composite. (2020) - Usha Rani, P.H.; Rajaprakash, B.M.; Mohan, N.; Akshay Prasad, M.
Abstract: The effect of hybrid powder fillers (WC + Ta/NbC) on thermal response and erosion wear resistance of woven glass fiber reinforced-epoxy composites has been studied. Vacuum assisted resin transfer moulding (VARTM) method was used to fabricate a set of GE composite specimen. Erosion wear test was carried out using alumina erodent, impinging at 40 m/s velocity, from a distance of 10 mm, at ambient and above glass transition temperatures. The rate of erosion was assessed at impingement angles 30°, 60° and 90°. The thermal stability of the composite samples and their response to heat was analysed by using thermal analysis methods TGA and DSC. The erosion wear mechanism of the composites was established by inspecting the eroded surface with the help of scanning electron microscopy.